Pengaruh Lingkungan Kerja, Kompensasi Dan Kepuasan Kerja Terhadap Komitmen Organisasi Perangkat Desa Di Kecamatan Ilir Talo Kabupaten Seluma - Hartono, Lovi; Islamuddin, Islamuddin (Jurnal Fokus Manajemen, 2024)
The title of this study is the effect of work environment, compensation and job satisfaction on the organizational commitment of village officials in the Ilir Talo sub-district of Seluma Regency. This research is based on the importance of organizational commitment in an organization. Several factors that influence organizational commitment are work environment, compensation, and job satisfaction. This study aims to analyze the effect of work environment, compensation, and job satisfaction on organizational commitment.This type of research is quantitative research with a descriptive approach. The population of this study were all village employees in Ilir Talo sub-district, Seluma district. The number of research samples was 90 people. Data collection was carried out using a questionnaire. Data analysis techniques using multiple linear regression analysis techniques.The results of data analysis obtained multiple linear regression equations as follows: Y = 2.387 + 0.175 X1 + 0.268 X2 + 0.092 X3. The results of the analysis show that the work environment has a positive and significant effect on organizational commitment, compensation has a positive and significant effect on organizational commitment, and job satisfaction has a positive and significant effect on organizational commitment. Simultaneously, work environment, compensation, and job satisfaction have a significant effect on organizational commitment.It is recommended that the village head be able to increase the organizational commitment of village officials by creating a positive work environment, improving the welfare of village officials, and increasing the job satisfaction of village officials, especially in terms of promotion.